The Bitterest Pills - Moncrieff, J. author. aut Link
XIV, 278 p.
Keywords: A challenging reappraisal of the history of antipsychotics, revealing how they were transformed from neurological poisons into magical cures, their benefits exaggerated and their toxic effects minimized or ignored.